The Effect of Crime and the Social Culture of the Community on Rural Development - Lodewik Zet (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
Crime has a significant influence on people’s lives. Not only on the social aspect, but crime will also affect regional development. In addition, socio-cultural factors have an essential role in developing rural communities. This study aims to determine the effect of crime and social culture on rural development. The method used in this study is Ordinary Least Square (OLS) followed by Chi-squared Automatic Interaction Detector (CHAID) to determine the segmentation of crime and socio-cultural factors of society towards rural development. The results of this study state that nationally all independent research variables have a significant effect on the 2018 Rural Development Index, with an R-squared value of 31.9%. Changes in the development category can be spurred through development focusing on underdeveloped and far from urban areas. The government also needs to pay attention to rurally located forest areas. Furthermore, the government needs to improve security in the community. Guaranteed security can create good development in the short and long term. In addition, the community needs to maintain cultural diversity through social interaction because it positively affects rural development.